ASYMPTOMATIC BACTERIURIA IN PREGNANCY: Asymptomatic Bacteriuria - Haider, Gulfareen; Rani, Shazia; Ghaffar, Saima; Haider, Ambreen (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency and risk factors of asymptomatic bacteriuria during pregnancy. Study Design: Descriptive study Place and Duration of Study: In obstetric and gynecology outpatient department of Isra university hospital Hyderabad Sindh from 2nd July to 10th December 2007. Patients and Methods: Total 111 women were included in the study. Inclusion criteria were pregnant women with no clinical features suggestive of UTI. Symptomatic women, women with any medical or renal disease and those who had taken antibiotics in last 6 weeks were excluded from the study. Dipstick test was performed on MSU and urine was cultured incase of positive dipstick. Data was analyzed on SPSS version 11. Frequencies were runned and chi-square test was used as test of significance. Results: A total of 111 women fulfilling the inclusion criteria were interviewed and tested for bacteriuriab Out of them 10 (9%) had bacteriuria. Out of them 10% were below 20 years and 90% were between 20-30 years (p=0.17). Regarding education 10% were literate and 90% were illiterate (p=<0.001). Prevalence of bacteriuria was 100% in women who had past history of urinary tract infection (p=0.004). 80% of women who were sexually active had bacteriuria while 20% had not (p=0.006). No association of bacteriuria was found with anemia, age, parity and socioeconomic condition. Conclusion: Asymptomatic bacteriuria is a common infection during pregnancy, have strong association with education, past history of urinary tract infection and illiteracy.